Zentrum und Peripherie in der deutschen Syntax.: Das Beispiel der Satzarten des Deutschen - Näf, Anton (Linguistik Online, 2021)
In Linguistik online 2021, I presented a four-level centre-periphery model of German syntax (with the categories “prototype”, “variants”, “competitive forms” and “free stylistic variation”) and tested and refined it on the basis of two well-researched grammatical phenomena, conditionality and passive structures. In the present paper, this model is applied to the sentence types of German, with comparative side glances at English and French. The model proves to be particularly fruitful in the functional area of exclamation, where a great variety of forms can be observed. I argue here that scientific grammars should not only record the form inventory of sentence types but should supplement this with information on their frequency of occurrence, especially with key figures on the relative proportions of the individual structures in their functional field of competition, broken down by different communicative situations or text types. The motto for the grammar writing of the future should be: From the “structures” to the “structures in use”.